Perkembangan Kurikulum Pendidikan Di Indonesia: Prinsip Dan Faktor Yang Mempengaruhi - Marzuqi, Badrul Munir; Ahid, Nur (JoIEM (Journal of Islamic Education Management), 2023)
Abstract The curriculum is a key in the implementation of educational activities because it relates to determining the direction, content and process of education, which ultimately determines the types and qualifications of graduates of an educational institution. Curriculum development is a must as a form of positive-conceptual response considering the influence of scientific and technological developments, which are in line with the increasingly complex developments of the era. History records that there were eleven changes to the post-independence Indonesian curriculum, starting from the 1947 lesson plan curriculum, then the 1952 unraveled lesson plan curriculum, the 1964 education plan curriculum, the 1968 curriculum, the 1975 curriculum with the term unit of study, the 1984 curriculum with the CBSA concept, the 1994 curriculum, the 2004 KBK curriculum, the KTSP curriculum, the 2013 curriculum and most recently the independent curriculum. Curriculum development must be based on principles that include general principles in the form of principles of relevance, flexibility, effectiveness, efficiency, continuity, goal-oriented, lifelong education, synchronization, integrity, objectivity, and democracy. Specific principles include setting goals, content, learning experiences, and assessment. Factors that influence curriculum development include university factors, community factors and societal values ​​or norms. In addition, there are philosophical, psychological, socio-cultural, political, state development and world development, as well as science and technology factors. Abstrak Kurikulum merupakan sebuah kunci dalam pelaksanaan kegiatan pendidikan karena berkaitan dengan penentuan arah, isi dan proses pendidikan yang pada akhirnya menentukan macam dan kualifikasi lulusan suatu lembaga pendidikan. Pengembangan kurikulum merupakan satu keharusan sebagai bentuk respon positif-konseptual mengingat pengaruh perkembangan ilmu pengetahuan dan teknologi yang sejalan dengan perkembangan zaman yang semakin kompleks. Sejarah mencatat ada sebelas kali perubahan kurikulum pasca kemerdekaan Indonesia, mulai dari kurikulum rencana pelajaran 1947, kemudian menjadi kurikulum rencana pelajaran terurai 1952, kurikulum rencana pendidikan 1964, kurikulum 1968, kurikulum 1975 dengan istilah satuan pelajaran nya, kurikulum 1984 dengan konsep CBSA, kurikulum 1994, kurikulum KBK tahun 2004, kurikulum KTSP, Kurikulum 2013 dan yang terbaru kurikulum merdeka. Pengembangan kurikulum harus berdasarkan pada prinsip-prinsip yang meliputi prinsip-prinsip umum berupa prinsip relevansi, fleksibilitas, efektivitas, efisiensi, kontinuitas, berorientasi pada tujuan, pendidikan seumur hidup, sinkronisasi, integritas, objektivitas, demokrasi. Prinsip khusus meliputi penyusunan tujuan, isi, pengalaman belajar, dan penilaian. Faktor-faktor yang mempengaruhi pengembangan kurikulum diantaranya faktor perguruan tinggi, faktor masyarakat dan faktor nilai atau norma masyarakat. Selain itu ada faktor filosofis, psikologis, sosial budaya, politik, pembangunan negara dan perkembangan dunia, serta ilmu pengetahuan dan teknologi.